Financial Literacy dan Mental Budgeting Terhadap Financial Well-Being: Peran Mediasi Investment Decision Making - Dhiny Rahmawati Mustapa; Muhammad Ali Fikri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The development of digital technology has influenced the financial behavior patterns of society. Although financial information is easily accessible, many individuals still face challenges in making wise investment decisions and achieving stable financial well-being. This study aims to analyze the influence of financial literacy and mental budgeting on financial well-being with investment decision making as a mediating variable. The sample of this research is 130 Generation Z investors in Yogyakarta. The sampling in this study used purposive sampling techniques with several criteria. Data were collected using questionnaires and analyzed through the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with Smart PLS 4.0 software. The instrument testing included validity and reliability tests. Hypothesis testing results show that financial literacy and mental budgeting have a positive effect on financial well-being, both directly and indirectly through investment decision making. Moreover, investment decision making is proven to be a significant mediator in the relationship between financial literacy and mental budgeting toward financial well-being. These findings support the theory of planned behavior framework, which states that attitudes, perceived behavioral control, and individual intentions play an important role in shaping financial behavior oriented toward well-being.